1999
DOI: 10.1071/pp98121
|View full text |Cite
|
Sign up to set email alerts
|

The maize transcription factor Sn alters proanthocyanidin synthesis in transgenic Lotus corniculatus plants

Abstract: Lotus corniculatus L. plants were transformed with Agrobacterium rhizogenes binary vector carrying the maize Sn regulatory gene driven by the 35S promoter. These plants showed modifications in the pattern of accumulation of proanthocyanidin (PA). All the transformed plants but one showed an increase in PA content in the root relative to control untransformed and control gus gene transformed plants (C). With respect to the PAaccumulation in leaves, Sn transgenic plants were grouped in two classes: suppressed (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The slight color difference between ban and ban tt12 possibly reveals a capacity of TT12 to transport anthocyanins as well, but to a small extent. These data may provide experimental support for the model proposed by Damiani et al (1999) in which catechin and procyanidin precursors accumulate in vacuoles before being polymerized to procyanidins.…”
Section: The Tt12 Gene May Be Involved In Vacuolar Transport Of Flavosupporting
confidence: 66%
See 1 more Smart Citation
“…The slight color difference between ban and ban tt12 possibly reveals a capacity of TT12 to transport anthocyanins as well, but to a small extent. These data may provide experimental support for the model proposed by Damiani et al (1999) in which catechin and procyanidin precursors accumulate in vacuoles before being polymerized to procyanidins.…”
Section: The Tt12 Gene May Be Involved In Vacuolar Transport Of Flavosupporting
confidence: 66%
“…The slight color difference between ban and ban tt12 possibly reveals a capacity of TT12 to transport anthocyanins as well, but to a small extent. These data may provide experimental support for the model proposed by Damiani et al (1999) in which catechin and procyanidin precursors accumulate in vacuoles before being polymerized to procyanidins.Flavonoids are synthesized in the cytoplasm at the level of the endoplasmic reticulum (Burbulis and Winkel-Shirley, 1999) and around the vacuoles (D. Saslowsky and B. WinkelShirley, personal communication) before their deposition in other cell compartments. The fact that PAs have been reported to reach the vacuole in vesicles derived from the endoplasmic reticulum (Baur and Walkinshaw, 1974;Parham and Kaustinen, 1977; Zobel, 1986;Ibrahim, 1992) is puzzling.…”
supporting
confidence: 66%
“…In Lotus corniculatus the maize anthocyanin regulatory gene Sn was introduced. Some plants were obtained with reduced foliar proanthocyanidin which may be of benefit in some agronomic situations (Damiani et al, 1999).…”
Section: Introduction Of Agronomically Useful Traitsmentioning
confidence: 99%
“…Several studies have reported increasing or decreasing the levels of PAs in tissues in which these compounds occur naturally (Bavage et al. , 1997; Damiani et al. , 1999; Robbins et al.…”
Section: Introductionmentioning
confidence: 99%